What’s in a name? The messy taxonomy of Oryza sp. and how it has impacted our archaeobotanical modelling of rice domestication - J. Bates (Quaternary Environments and Humans)
The domestication of our major cereals has been the focus of numerous branches of science. While some, such as wheat and barley, have fairly established pathways and histories, others remain open to debate, and Oryza sativa, Asian rice, ranks high amongst them. Two main hypotheses have arisen – that rice was domesticated initially in China and carried the genes for domestication to other regions as the crop was traded during the Bronze Age (often called the ‘proto-indica’ hypothesis), the other that rice was independently domesticated in China forming japonica and also in India forming indica. Both hypotheses however have their own challenges around data, but at the heart of them is a key issue that they are not starting at the same taxonomic base – the founder wild ancestor of rice in India remains debated. In this paper the messy taxonomies of rice, both wild and domesticated, are outlined, and the implications of this on the archaeological modelling of rice domestication are unpacked. Only once an established and agreed foundation for assessing these two hypotheses is agreed can they be addressed. The paper outlines how both hypotheses need to be addressed moving forwards using archaeological, (archaeo)botanical, archaeochemical, (archaeo)genetic and other forms of data moving forwards.